PLANTS - Legg, Gerald; Weston, Steve; Channel, Jim; Miles, Elizabeth (Worksop : Award Publications Ltd, 2022)
The amazing world of plant life is full of incredible surprises. Discover how plants are fundamental to the survival of all life on Earth, and the amazing ways they have adapted to thrive everywhere from forests and mountainsides to ponds, oceans and arid deserts. With stunning photographs and cutaway illustrations, How It Works: Plants explores the fascinating world of flowers, trees, leaves and seeds. Clear explanations and awesome facts reveal everything from the secrets inside flowers and plant cells, to the layers of life in a rainforest
Includes index
For ages 7-9 years.
Keywords: Plants -- Juvenile literature; Juvenile works